The German and Belgian accreditation models for diabetic foot services. (January 2016) - Morbach, Stephan; Kersken, Joachim; Lobmann, Ralf; Nobels, Frank; Doggen, Kris; Van Acker, Kristien
Abstract: The International Working Group on the Diabetic Foot recommends that auditing should be part of the organization of diabetic foot care, the efforts required for data collection and analysis being balanced by the expected benefits. In Germany legislature demands measures of quality management for in‐ and out‐patient facilities, and, in 2003, the Germany Working Group on the Diabetic Foot defined and developed a certification procedure for diabetic foot centres to be recognized as 'specialized'. This includes a description of management facilities, treatment procedures and outcomes, as well as the organization of mutual auditing visits between the centres. Outcome data is collected at baseline and 6 months on 30 consecutive patients. By 2014 almost 24 000 cases had been collected and analysed. Since 2005 Belgian multidisciplinary diabetic foot clinics could apply for recognition by health authorities. For continued recognition diabetic foot clinics need to treat at least 52 patients with a new foot problem (Wagner 2 or more or active Charcot foot) per annum. Baseline and 6‐month outcome data of these patients are included in an audit‐feedback initiative. Although originally fully independent of each other, the common goal of these two initiatives is quality improvement of national diabetic foot care, and hence exchanges between systems has commenced. In future, the German and Belgian accreditation models might serve as templates for comparable initiatives in other countries. Just recently the International Working Group on the Diabetic Foot initiated a working group for further discussion of accreditation and auditing models (International Working Group on the Diabetic Foot AB(B)A Working Group). Copyright © 2016 John Wiley & Sons, Ltd.